Tubuh sebagai Manifesto: Pandangan Politik Sally Rooney dalam Normal People - Dewi, Chintya; Ferdinal, Ferdinal; Sudarmoko, Sudarmoko (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This research explores the role of the body in the Irish literary work, Normal People. Written by renowned Irish author Sally Rooney, the novel narrates how contemporary Irish society experiences shifts in its social structure. It delves into the lives of young Irish characters as they navigate social and political upheaval in relation to the Western culture that serves as their cultural axis. This culture is, in part, represented through the colonized form of the body. Rooney elevates this concept to emphasize her political stance that the body has become a manifesto in the ideological struggle against the encroaching Western influences. By employing Lucien Goldmann’s theoretical framework, this article demonstrates the intersection of the body and alcohol, connecting the historical memory of the Republic of Ireland with Northern Ireland. Moreover, the article contends that the United States of America has colonized the bodies of the Republic of Ireland’s society through the consumer patterns of popular culture introduced in television advertisements.Keywords – Alcohol, Colonization, Political Beliefs, Popular Culture, Television Commercials.